IMPLEMENTASI PENGELOLAAN DANA DEPOSITO PT. BPR SENTRAL MANDIRI - Rahmat Yuliansyah,; R. Roro Nurfatihah, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the procedures for managing deposits and how to calculate the results of deposit management and the risks that may be present in deposits at PT. BPR Sentral Mandiri. This study uses a qualitative method that covers various aspects, such as analysis of procedures and management of deposits at BPR, starting from the opening process, setting interest rates, to policies related to deposits, this study will also explore the perception and motivation of the community in choosing deposits as a form of investment, including their level of satisfaction. In addition, it will be traced how funds obtained from deposits affect the distribution of credit by BPR to the community. This study also aims to identify the advantages and challenges faced by customers and BPR in managing deposits. finally, the deposit marketing strategy implemented by BPR to attract public interest will be an important part of this study. The results of the study, management of PT. BPR Sentral Mandiri is in accordance with OJK Regulation Number 4 / POJK.03 / 2015. and Number 13 / POJK.03 / 2015 concerning the implementation of BPR risk management